2014
DOI: 10.1097/sap.0b013e318269e4ee
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combined Skin Sparing Mastectomy and Immediate Subpectoral Prosthetic Reconstruction on the Pectoralis Major Muscle Function

Abstract: Daily life consequences of partial detachment of the pectoralis major muscle were acceptable in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
1
16
1
3
Order By: Relevance
“…However, both fiber regions of the pectoralis major are being underutilized in subpectoral implant patients when compared to healthy controls. These findings contrast previous data that showed increased activity in the clavicular fiber region post‐reconstruction when compared to pre‐reconstruction levels during maximal voluntary contractions . Future work should further investigate the long‐term neuromuscular adaption of shoulder musculature to subpectoral implant breast reconstruction.…”
Section: Discussioncontrasting
confidence: 97%
“…However, both fiber regions of the pectoralis major are being underutilized in subpectoral implant patients when compared to healthy controls. These findings contrast previous data that showed increased activity in the clavicular fiber region post‐reconstruction when compared to pre‐reconstruction levels during maximal voluntary contractions . Future work should further investigate the long‐term neuromuscular adaption of shoulder musculature to subpectoral implant breast reconstruction.…”
Section: Discussioncontrasting
confidence: 97%
“…This can be explained because all the women had undergone or were undergoing physical therapy as a follow-up to cancer treatment; also, the women with lymphedema, which is known to be a comorbidity that interferes with functionality 28 , were excluded from the research. Previous studies have reported that after breast reconstruction women may experience decreased functionality 29,30 , however, one study reported no association between breast reconstruction and functionality 3 , which corroborates the results of this research. Such findings can be explained by the fact that the sample studied had an almost two-year long postoperative period, which could have minimized the treatment's effects.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, the better cosmetic is associated with the same loss of muscle function present with the use of expander and physiotherapy sessions are often required after both procedures . About 16% of reconstructed patients experience decreased pectoralis strength during postoperative isometric muscle tests …”
Section: Discussionmentioning
confidence: 99%
“…20 About 16% of reconstructed patients experience decreased pectoralis strength during postoperative isometric muscle tests. 21,22 With the aim of avoiding the pectoralis major impairment, a muscle-sparing breast reconstruction technique has been proposed by with the subcutaneous tissue. 11,12 Despite the prepectoral reconstructive technique was reported by some authors also with other materials, 14,15,23 we performed the study with the Braxon ADM because it is the only matrix approved for this specific indication and its preshaped feature has several advantages.…”
Section: Discussionmentioning
confidence: 99%